HEARTS IN RHEUMATOID ARTHRITIS: THE RELATIONSHIP WITH IMMUNOLOGICAL DISORDERS - Ergasheva Ma’mura Toshtemirovna; Khusainova Munira Alisherovna; Yarmatov Suvon Totlibayevich; Ergashova Madina Muxtorovna (Journals Park Publishing, 2022)
Rheumatoid arthritis (RA) is a chronic systemic inflammatory disease of connective tissue with progressive damage mainly to peripheral (synovial) joints by the type of symmetrical erosive—destructive polyarthritis with frequent extra-articular manifestations, among which heart damage, according to autopsy data, is noted in 50-60% of cases. Changes in the heart in RA in in the recent past, it was isolated into the articular-cardiac form of the disease. When the joints are affected, when physical activity is noticeably reduced, cardiac pathology is often masked, which requires a more attentive and thorough examination of the patient from the doctor. At the same time, clinical changes on the part of the heart, as a rule, are minimal and rarely come to the fore in the overall picture of the underlying disease. Systemic manifestations of RA, including heart damage, determine the prognosis as a whole, therefore, their early recognition and targeted treatment are important.  The frequency of myocardial damage in RA in the form of myocarditis has not been clarified. This is due, on the one hand, to the difficulty of diagnosing myocarditis in people with limited motor activity, on the other — the lag of clinical manifestations from morphological changes of the heart. The pathology of the myocardium is polymorphic in nature due to the presence of various vascular lesions. In some vessels there is vasculitis, in others — hyalinosis, in others — sclerosis. The nature of vasculitis can be proliferative and rarely proliferative-destructive. In the inflammatory infiltrate, lymphohistiocytic elements predominate both in the perivascular space  and in the vascular wall. It should be noted that when the main process is activated, a combination of old and fresh vascular changes is observed.
Keywords: heart disease; atherosclerosis; rheumatoid arthritis